The most severe forms of type I autoimmune hepatitis are associated with genetically determined levels of TGF-β1 - Paladino, Natalia (2010)
We previously reported that paediatric (PAH) and adult (AAH) forms of type I autoimmune hepatitis (AH) have different HLA-associations and clinical outcome. In the present study we investigated the role of TGF-β1 genetic polymorphisms in the different outcome of PAH and AAH. We found a significant increase of "high producer" 25GG genotype in PAH and 10CC in AAH. Low inflammation and low fibrosis in AAH was associated with the increase of codon 10CC (high producer) and codon 25CC (low producer) genotypes. The analysis in AAH of the two positions-haplotypes revealed that combined presence of 25GG and 10CC seems to neutralize the 10CC effect which remained in AAH having the 10CC+-25GG- haplotype. Altogether these results may explain, at least partially, the different clinical outcome of AAH and PAH.